Postal system strategy selection by applying multicriteria analysis - Petrović, V. (Yugoslav Journal of Operations Research; Vol 16 No 2 (2006): Vol. 16 No. 2, 2016)
The paper presents the methods by which postal organizations adapt strategically to significant changes in the external environment in order to survive on the market and gain new possibilities for prosperity. It is proved that only planned changes can accelarate the speed of adjustment to new conditions. By studying environment demands and the ways postal administrations have implemented changes, it can be concluded that there exists a general model of postal system transformation. After reviewing the available transformation scenarios that are applicable to all postal operators, the paper proposes the selection of postal system development strategy by applying multicriteria analysis.